Older adults in the Internet – Internet addiction and its intrapsychic correlates - Wójciak, Aleksandra (Kwartalnik Naukowy Fides et Ratio, 2022)
The aim of the study was to verify the relationship between Problematic Using of the Internet and its selected intrapsychic correlates in a group of people in late adulthood. The analyses conducted so far respond to an insufficient number of domestic and foreign publications on this subject.Statistical analysis was applied to the results of the study carried out among a group of 44 seniors (the average age 67 years old). The control group consisted of 41 middle adults (the average age was 35). The study applied: Test of Problematic Using of the Internet, Coping Inventory - Mini-COPE, The IPIP-BFM-20 Questionnaire and Brief Resilience Coping Scale. The results of the study have shown a significant correlation between the problematic using of the Internet (PUI) in the surveyed group of seniors and specific strategies of dealing with stress: self-blame (p